In vitro antifungal activity of Myracrodruon urundeuva Allemao against human vaginal Candida species - De Oliveira, Fernando A.; Rorato, Vanessa C.; Almeida-Apolonio, Adriana A.; Rodrigues, Allan B.; De Barros, Aline L.; Sangalli, Andreia; Arena, Arielle C. [UNESP]; Mota, Jonas S.; Grisolia, Alexeia B.; De Oliveira, Kelly M. P. (Acad Brasileira De Ciencias, 2017)
Myracrodruon urundeuva is a plant native to Brazil, which is used by the indigenous population for the treatment of candidiasis. The aims of this study were to evaluate the antifungal activity of extract against human vaginal Candida species and evaluate the possible toxicological activities of M. urundeuva. Initially, ethanol extracts, ethyl acetate fractions, and hydroalcoholic fractions of the bark and leaf of M. urundeuva were used to determine the minimum inhibitory concentration. The extracts that showed antifungal activity were characterized by liquid chromatography and subjected to toxicity assessment. Toxic, cytotoxic, genotoxic, and mutagenic testing were performed using Allium cepa and Ames assays with the ethanol extracts of the bark and leaves. Hemolytic activity was evaluated in erythrocytes and acute toxicity in rats. The ethanol bark extracts showed best activity against Candida albicans, C. krusei, and C. tropicalis ATCC (4-512 mu g/mL). Chemical characterization indicated the presence of flavonoids and tannins in the extracts. Hemolytic activity, genotoxicity, and mutagenicity were not observed. The results of the Ames and A. cepa tests were also in agreement, ethanol bark extracts and ethanol leaf extracts of M. urundeuva showed absence of mutagenic activity. Similar results were observed in the A. cepa assay and acute toxicity test in rats. M. urundeuva bark extracts showed potential for the treatment of vaginal infections caused Candida species, as a topical.
Keywords: Anacardiaceae; candidiasis; Myracrodruon urundeuva; traditional medicine